Climate change, its effects and actions in the light of the fourth assessment report of the IPCC - Nováky, Béla (Tájökológiai Lapok, 2009)
The Fourth Assessment Report of the Intergovernmental Panel of Climate Change (IPCC), published in 2007 stated that the climate of the Earth had been warming since the industrial revolution. A highly probable cause for this warming is the increasing amount of greenhouse gases, notably carbon dioxide as a consequence of various human activities. If this emission keeps its current measure or even increases, the extent of global warming may exceed 2,5–5,5 °C until the end of the 21st century. Global warming will have effects on regional climate, natural physical and biological systems and human systems. Several signals indicate that these changes have already started. As a consequence of warming, polar ice is melting, area of glaciers and permafrost is decreasing, sea level is rising, usable water stock is decreasing in areas with dry climate, extremities in weather (drought, floods) become more frequent. Climate change, together with non-climatic effects (land use changes, pollutions, mass exploitation of natural resources), threatens several ecosystems, especially in case of warming by more than 2–3 °C. Biogeographical zones are shifting; e. g. forests expand onto tundra areas and subtropical areas onto tropics. Climate change threatens biodiversity as well; 20–30% of known species may disappear. As a consequence of warming seas, a sharp rate of coral crawls may disappear, territory of some species may decrease due to polar ice melting, mangrove ecosystems are endangered by rising sea level. Considering human sphere, number of people living in areas with water shortage is increasing, safety of food supply is declining at a longer period, and risk of infectious diseases is growing. Sea level rise threatens the safety of several million shore inhabitants. There are two ways to avoid or reduce harmful effects of climate change: one is mitigation of climate change, the other is adaptation to new climatic conditions. Az Éghajlat-változási Kormányközi Testület (IPCC) 2007-ben közreadott Negyedik Értékelő Jelentése ...